(untitled) (Journal of Engineering, 2020)
Bored piles settlement behavior under vertical loaded is the main factor that affects the design requirements of single or group of piles in soft soils. The estimation of bored pile settlement is a complicated problem because it depends upon many factors which may include ground conditions, validation of bored pile design method through testing and validation of theoretical or numerical prediction of the settlement value. In this study, a prototype single and bored pile group model of arrangement (1*1, 1*2 and 2*2) for total length to diameter ratios (L/D) is 13.33 and clear spacing three times of diameter, subjected to vertical axial loads. The bored piles model used for the test was 2000 mm in length, and 150 mm in diameter has been constructed in soft clayey soils. Furthermore, different theoretical methods have been used for the estimation of bored pile settlement, such as Poulos and Vesic’s methods and then their comparison with the pile load test data based on the quick pile load test as presented in (ASTM-D1143, 2007). In general, the theoretical method for estimation the bored pile settlement by Poulos and Vesic’s gives higher value of the settlement for the single and group bored pile compared to the pile settlement results obtained from field pile load test data. Therefore, it is not recommended to be used for soft clayey soils. On the other hand, Hansen’s 90% and Butler and Hoy’s results may be considered reliable interpretation method to compute the settlement of single and group bored pile.